2020
DOI: 10.1038/s41598-020-72150-z
|View full text |Cite
|
Sign up to set email alerts
|

Study of diesel engine characteristics by adding nanosized zinc oxide and diethyl ether additives in Mahua biodiesel–diesel fuel blend

Abstract: This study deals with an experimental investigation to assess the characteristics of a modified common rail direct injection (CRDI) engine utilizing diesel, Mahua biodiesel, and their blends with synthesized zinc oxide (ZnO) nano additives. The physicochemical properties of diesel, diesel + 30 ppm ZnO nanoparticles (D10030), 20% Mahua biodiesel (MOME20), and Mahua biodiesel (20%) + 30 ppm ZnO nanoparticles (MOME2030) were measured in accordance to the American Society for Testing and Materials standards. The e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(37 citation statements)
references
References 68 publications
0
32
0
Order By: Relevance
“…To stabilise the blend, sodium dodecyl sulphate (SDS) surfactant was used for the ultrasonication process. The process was adapted from previous investigations by Soudagar et al [2,3]. Initially, 25% of soybean biodiesel was blended with 75% diesel using an ultrasonication bath for 60 min.…”
Section: Preparation and Physicochemical Properties Of Nano Fuel Blendsmentioning
confidence: 99%
See 1 more Smart Citation
“…To stabilise the blend, sodium dodecyl sulphate (SDS) surfactant was used for the ultrasonication process. The process was adapted from previous investigations by Soudagar et al [2,3]. Initially, 25% of soybean biodiesel was blended with 75% diesel using an ultrasonication bath for 60 min.…”
Section: Preparation and Physicochemical Properties Of Nano Fuel Blendsmentioning
confidence: 99%
“…The current scenario of increasing fuel prices and depletion of fossil fuels has increased demand for renewable energy in the industry and heavy-duty diesel engines [1][2][3]. Biodiesel is one of the potential sources of clean and green energy for today's world's sustainable development [4].…”
Section: Introductionmentioning
confidence: 99%
“…It has observed that BTEis decreased in higher blend ratios. The calorific values of fuel lead to increasing the efficiency of an engine [18]. Brake Specific Energy Consumption Brake Specific Energy Consumption (BSEC) is equal to the product of Brake Specific Fuel Consumption (BSFC) and Calorific Value (CV) of the fuel.It is one of the engine parameters for measuring the engine fuel consumption by energy thusit means that how efficiently energy from fuel is obtained.…”
Section: Results and Discussion Brake Thermal Efficiencymentioning
confidence: 99%
“…The uncertainties and accuracies of the measured parameters in the current investigations are given in Table 3 . The calculation for uncertainty for brake-specific fuel consumption is based on the systematic set of procedures available in open literature [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The uncertainties and accuracies of the measured parameters in the current investigations are given in Table 3. The calculation for uncertainty for brake-specific fuel consumption is based on the systematic set of procedures available in open literature [25]. The variance of the measured factors estimated utilizing Gaussian distribution as described in Equation 1, under the of limits confidence of ±2σ.…”
Section: Uncertainty Analysismentioning
confidence: 99%